Perspective of Islamic Religious Education Study Program Students on the Islamic Education Curriculum in Indonesia - Alfian, Muhammad; Herningrum, Indah; Putra, Pristian Hadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study investigates the perceptions of final-year students in the Islamic Religious Education (PAI) Study Program at IAIN Kerinci regarding the evolution, structure, and implementation of the Islamic education curriculum in Indonesia. Employing a qualitative research approach with a case study design, the research seeks to provide an in-depth and contextually grounded understanding of student experiences within a specific institutional setting. Data were collected using triangulated methods, including in-depth semi-structured interviews, participant observation, and document analysis. A total of ten final-year students—purposively selected based on academic performance and active participation in academic and co-curricular activities—were interviewed to gain reflective insights into how the curriculum aligns with professional teaching demands. The findings reveal that while students acknowledge the curriculum’s foundational role in shaping moral character and professional competencies, they also identify significant disjunctions between policy intentions and classroom realities. Key issues include outdated content, limited digital literacy integration, lack of interdisciplinary approaches, and inadequate preparation for real-world teaching challenges. Students perceived that current curricula overemphasize theoretical knowledge while underpreparing them for professional demands such as inclusive education, contextual pedagogy, and technological adaptation. Despite progressive reforms like the Merdeka Curriculum, institutional readiness and lecturer capacity remain major barriers to effective implementation. This study contributes to curriculum discourse by centering student voices and emphasizing the need for learner-inclusive reform in Islamic higher education. The findings suggest that involving students as active stakeholders in curriculum design is essential for achieving contextual, adaptive, and competency-based Islamic education.